For Males Only? The Search for Serious, Violent, and Chronic Female Juvenile Offenders - Wolff, Kevin T. (Journal of developmental and life-course criminology, 2017)
The current study examines the prevalence and correlates of serious, violent, and chronic offending among female juveniles admitted to juvenile justice residential programs in the state of Florida.